Retrospective analysis of the causes of early neonatal infection and strategy for the prevention of early neonatal morbidity and mortality - El Kandoussi Sara (Запорізький державний медичний університет, 2021)
Introduction. There is a close relation between the infectious colonization of the mother and her child. The frequency of infection during childbirth through the natural birth canal is 50-60%. Aim of the work is to analyze the causes of early neonatal infection in the maternity hospital and justify ways of prevention.